Penguatan Promosi Melalui Media Website pada Hotel Alvina Pematangsiantar - Djoni; Roni Yunis; Suminar Ariwibowo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The partner in the Community Service Program (PkM) is Hotel Alvina Pematangsiantar. Seeing the need for Hotel Alvina for the use of information technology that seems not optimal, especially in supporting media ads platform. To support a better promotion, it is necessary to have a website that can increase the capacity of promotion and visitors. The implementation of the PkM program refers to a qualitative approach and is combined with the stages in the Software Development Lifecycle which have been modified into 6 stages, starting from initiation, design, data migration, development, implementation, and maintenance. The resulting website can be used by Hotel Alvina to manage hotel information, such as contact us, about us, blogs, and galleries. The website is also supported by online reservation facilities that can be used by visitors. The website that has been successfully implemented is expected to increase services and promotions for Hotel Alvina, so that it can compete and develop in a sustainability.